Gait assist brace with double carbon fiber reinforced plastic spring blades to allow ankle joint movement and change in walking direction. (3rd August 2021) - Takeda, Iwori; Yasunaga, Wataru; Kobayashi, Satoshi; Tagawa, Yusaku; Onodera, Hiroshi
Abstract : Unpowered braces and exoskeletons, which are often made of carbon fiber reinforced plastic (CFRP), can assist lower limb movements and can be worn permanently. Furthermore, braces to be worn at all times must not hinder the change of direction, as this movement is nearly as essential as straight gait in daily life. Ankle joint movements, especially inversion and eversion, play a key role in changing the direction during walking. However, in the case of conventional short leg braces, the range of motion is limited because the single wide CFRP blade placed at the back of the leg cannot deform elastically. In this study, a gait assist system with two CFRP blades on the lateral and medial sides of the leg was developed. The system could effectively assist the gait and did not inhibit the change in the direction. GRAPHICAL ABSTRACT: UF0001